Low Noise Amplifier at 5.8GHz with Cascode and Cascaded Techniques Using T-Matching Network for Wireless Applications - Ibrahim , A.B; Othman , A.R; Hussain , M.N; Johal , M.S (2011)
This paper present a 5.8 GHz low noise amplifier (LNA) design with cascode and cascaded techniques using T-matching network applicable for IEEE 802.16 standard. The amplifier use FHX76LP Low Noise SuperHEMT FET. The design simulation process is using Advance Design System (ADS) software. The cascode and cascaded low noise amplifier (LNA) produced gain of 36.52dB and noise figure (NF) at 1.2dB. The input reflection (S11) and output return loss (S22) are -21.1dB and -27.7dB respectively. The bandwidth of the amplifier is more than 1GHz. The input sensitivity is complying with the IEEE 802.16 standards.